Unions, Equity, and the Path to Renewal - Foley, Janice R.; Baker, Patricia L. (UBC Press, 2009)
Trade unions in Canada are losing their traditional support base, and membership numbers could sink to US levels unless unions recapture their power. Unions, Equity, and the Path to Renewal brings together a distinguished group of union activists and equity scholars who trace how traditional union cultures, practices, and structures have eroded solidarity and activism and created an equity deficit in Canadian unions. Informed by a feminist vision of unions as instruments of social justice, the contributors argue that equity within unions is not simply one possible path to union renewal – it is the only way to reposition organized labour as a central institution in workers’ lives. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/unionsequitypath0000unse
Keywords: Canada; Equality; Labor unions; Social aspects; Women in the labor movement